Surveillance for hepatocellular carcinoma with a 3-months interval in "extremely high-risk" patients does not further improve survival. Issue 7 (July 2022) - Pelizzaro, Filippo; Peserico, Giulia; D'Elia, Marco; Cazzagon, Nora; Russo, Francesco Paolo; Vitale, Alessandro; Giannini, Edoardo G.; Piccinnu, Manuela; Rapaccini, Gian Ludovico; Di Marco, Maria; Caturelli, Eugenio; Zoli, Marco; et al.
Abstract: Background: An enhanced surveillance schedule has been proposed for cirrhotics with viral etiology, who are considered at extremely high-risk of hepatocellular carcinoma (HCC). Aims: We compared the 3- and 6-months surveillance interval, evaluating cancer stage at diagnosis and patient survival. Methods: Data of 777 HBV and HCV cirrhotic patients with HCC diagnosed under a 3-months ( n  = 109, 3MS group) or a 6-months ( n  = 668, 6MS group) surveillance were retrieved from the Italian Liver Cancer database. Survival in the 3MS group was considered as observed and adjusted for lead-time bias, and survival analysis was repeated after a propensity score matching. Results: The 3-months surveillance interval neither reduced the share of patients diagnosed outside the Milano criteria, nor increased their probability to receive curative treatments. The median survival of 6MS patients (55.0 months [45.9–64.0]) was not significantly different from the observed (47.0 months [35.0–58.9]; p  = 0.43) and adjusted (44.9 months [33.4–56.4]; p  = 0.30) survival of 3MS patients. A propensity score analysis confirmed the absence of a survival advantage for 3MS patients. Conclusions: A tightening of surveillance schedule does not increase the diagnosis of early-stage tumors, the feasibility of curative treatments and the survival. Therefore, we should maintain the 6-months interval in the surveillance of viral cirrhotics.